2008
DOI: 10.1111/j.1365-3156.2008.02043.x
|View full text |Cite
|
Sign up to set email alerts
|

High efficacy of two artemisinin‐based combinations (artemether–lumefantrine and artesunate plus amodiaquine) for acute uncomplicated malaria in Ibadan, Nigeria

Abstract: Summaryobjective To test the hypothesis that artesunate plus amodiaquine (ASAQ) is as effective as artemether-lumefantrine (AL) in the treatment of acute uncomplicated malaria in Nigerian children.methods In an open label, randomized controlled clinical trial, children aged 6 months to 10 years were randomized to receive artesunate (4 mg ⁄ kg daily) plus amodiaquine (10 mg ⁄ kg daily) or AL (5-14 kg, one tablet; 15-24 kg, two tablets and 25-34 kg, three tablets twice daily). Both drug regimens were given for 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 17 publications
(22 reference statements)
6
26
0
Order By: Relevance
“…However, it should be borne in mind that Coartem is effective at treating malaria, with high success rates (Ͼ90 to 95%), in many areas where malaria is endemic, including Kenya (11,12,18,42). Thus, the mechanisms of Coartem resistance in vivo will likely involve other genes.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be borne in mind that Coartem is effective at treating malaria, with high success rates (Ͼ90 to 95%), in many areas where malaria is endemic, including Kenya (11,12,18,42). Thus, the mechanisms of Coartem resistance in vivo will likely involve other genes.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 With the adoption of these ACTs, small-scale studies have been frequent in the country, 29,30 but evaluation of relatively large numbers of children over a relatively long period is an exception. The present study attempted to rectify this deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The polymerase chain reaction (PCR) corrected day 28 cure rates per protocol of the two patient populations were 98.4% for AS-AQ and 100% for AL. Both drug combinations were well tolerated, the efficacy comparison demonstrated that AS-AQ was as effective as AL, and both combinations were shown to be both efficacious and safe [14].…”
Section: The Six-dose Regimen Of Al Is Similar To the Efficacy Achievmentioning
confidence: 94%